Prospects and Challenges of Information Resource Sharing Between Libraries in Nigeria - Agbato, E. F. (POMLIF Journal of Library and Information Science, 2019)
Resource sharing is a method of overcoming the limitations of the individual libraries in respect of their resources by way of co-operation and co-ordination among the participating libraries. In the recent past, resource sharing concept has prime factor and playing vital roles in libraries because of innovative developments in ICT. Resouce sharing has become a prime reason for establishing co-operation between libraries without any geographical barriers. With this backdrop, this paper attempts to discuss the concepts of resource sharing activities. It is also identified prospects and challenges of resources sharing in Nigeria for its underdeveloped infrastructure and consequences thereof. It brings out some suggestions for improvement.